Physicochemical qualities of stored fresh cut EVIARC sweet jackfruit (Artocarpus heterophyllus Lam.) pulp as influenced by deseeding, packaging method and storage condition - Pablo, Anne Gellie P.; Galvez, Lorina A.; Lauzon, Roberta D.; Diczbalis, Yan (Annals of Tropical Research, 2019)
Processing method plays a significant role in the physicochemical property of food products. This study evaluated the effects of deseeding, packaging method, and storage condition on the physicochemical properties of fresh-cut jackfruit during the 8-day storage period. A 2x2x2 factorial experiment was used in the study with a total of 8 treatments. All of the treatments were subjected to physicochemical analysis following standard protocols. Data were subjected to single factorial Analysis of Variance (ANOVA) and multi-factorial ANOVA for the interaction of dependent variables. Jackfruit pulps which were deseeded have shown significant decrease in the physicochemical attributes of the product which is an indicator for product quality. Deseeded products had much faster deterioration compared to treatments with intact seeds. Treatments stored in chilling (4-6oC) condition exhibited lesser variation in TA, TSS, pH, browning and firmness during the storage period compared to those stored at ambient temperature. Chilled treatments packed in vacuum had slower deterioration compared to treatments which were conventionally packed.